Definition of Biochemical Recurrence of Localized Prostate Cancer Following Radiotherapy: A Literature Review - Franca, Carlos Antônio da Silva (2008)
The American Society for Therapeutic Radiology and Oncology (ASTRO) conference was convened in 1996 with the purpose of defining biochemical PSA recurrence after radiotherapy for localized prostate cancer. The ASTRO consensus defines recurrent disease as three consecutive rises in PSA after a nadir, with date of failure as the point halfway between the nadir date and first rise. This definition is not related to clinical recurrence, disease progression, or survival rates. The importance of defining recurrent disease is that it determines the beginning of immediate salvage therapy. The ASTRO definition has been criticized worldwide, and there is no ideal, universally accepted definition for this disease entity. We conducted a literature review on this subject through Medline, Bireme, and Academic Google. The ASTRO consensus definition for recurrence must be applied in scientific studies with strict adherence to its recommendations, as well as in surveys of patients submitted to external beam radiotherapy or brachytherapy without hormone therapy. The PHOENIX consensus can be applied whenever external beam radiotherapy is used, with or without the combined hormone therapy.